The impact of tourist attractions and accessibility on tourists' satisfaction: The moderating role of tourists' age - Biswas, Chhanda; Omar, Hamimi; Rashid Radha, Jasmine Zea Raziah Radha (Editura Universitatii Din Oradea, 2020)
Age has frequently been recognized as one of the key attributes and indicators in creating an advertising system. In any case, it has been infrequently discovered the moderating effects of age on the links between attractions and accessibility as well as tourist satisfaction. Particularly, in the context of Bangladesh, this sort of study has not ever been considered. Hence, this study fulfils the gap by examining the moderating role of age in the relationship of these constructs. The questionnaire survey was directed for gathering data from international tourists in the Hazrat Shahjalal International Airport in Bangladesh. The outcomes got from Structural Equation Modeling (SEM) using the SmartPLS v3 uncovered that age significantly moderated the relationship between attraction and tourist satisfaction as well as accessibility and tourist satisfaction.